Numerical Investigation of the Impact of Processing Conditions on Burr Formation in Carbon Fiber-Reinforced Plastic (CFRP) Drilling with Multiscale Modeling - Bi, Guangjian; Wang, Xiaonan; Shi, Yongjun; Zhang, Cheng; Zhao, Xuejin (Materials, 2025)
Burrs generated during the drilling of carbon fiber-reinforced plastics (CFRPs) would seriously reduce the service life of the components, potentially leading to assembly errors and part rejection. To solve this issue, this paper proposed a finite element (FE) model with multiscale modeling to investigate the formation and distribution of burrs at various processing conditions. The FE model comprised the microscopic fiber and resin phases to predict the formation process of burrs, while part of the CFRP layers was defined to be macroscopic equivalent homogeneous material (EHM) to improve the computational efficiency. A progressive damage constitutive model was proposed to simulate the different failure modes and damage propagation of fibers. The impact of strain rate on the mechanical properties of the resin and CFRP layers was considered during the formulation of their constitutive models. With this numerical model, the formation process of the burrs and the drilling thrust force were accurately predicted compared to the experimental measurements. Then, the burr distributions were analyzed, and the influences of the drill bit structures and drilling parameters on burrs were assessed. It was concluded that the burrs were easily generated in the zones with 0° to 90° fiber cutting angles at the drilling exit. The sawtooth structure could exert an upward cutting effect on burrs during the downward feed of the tool; thus, it is helpful for the inhibition of burrs. More burrs were produced with higher feed rates and reduced spindle speeds.